2017
DOI: 10.1111/aen.12265
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour and survival of Bacillus thuringiensis‐resistant and Bacillus thuringiensis‐susceptible larvae of Helicoverpa armigera (Lepidoptera: Noctuidae) exposed to a diet with Bacillus thuringiensis toxin

Abstract: Although higher than expected numbers of surviving larvae of Helicoverpa spp. are reported in some Bollgard II cotton fields from time to time, there is no convincing evidence that field resistance has developed. A behavioural component, specifically the avoidance of the toxin, was considered to contribute to larvae surviving on Bacillus thuringiensis (Bt) toxin-expressing plants. Experiments were conducted with Bt-susceptible and Bt-resistant larvae of Helicoverpa armigera to investigate (1) how larval respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…In other cases, it is reported that larvae were reared in incubators (Luong et al . ) or under fluorescent light (Tessnow et al . ), although fluorescent light sources can differ from manufacturer to manufacturer in the peaks of their wavelength emissions, which are sharp and narrow compared to natural light (Longcore et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cases, it is reported that larvae were reared in incubators (Luong et al . ) or under fluorescent light (Tessnow et al . ), although fluorescent light sources can differ from manufacturer to manufacturer in the peaks of their wavelength emissions, which are sharp and narrow compared to natural light (Longcore et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Luong et al . ). Potential pest control and mitigation strategies have been proposed on the basis of these experiments (Reddy & Manjunatha ).…”
Section: Introductionmentioning
confidence: 97%
“…In the field it is not uncommon to find small groups of eggs on individual plant structures on cotton (Titmarsh, ) and the first hatched neonates could encounter their non‐hatched conspecific eggs. Such behavior could be adaptive as it would increase the likelihood of surviving the vulnerable first instar stage on plants that are poor hosts (Kyi et al, ), including Bt and non‐Bt cotton, but should not be interpreted as behavioral resistance without more detailed experiments (Zhao et al, ; Zalucki & Furlong, ; Luong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…They have been able to survive off the plant for at least 1 h, and travel up to 80 cm from where they dropped to the ground (for a similar finding see Terry et al, ). Under laboratory conditions larvae can go without food for 24 h and recover if they find suitable food (Luong et al, ). Larvae can also ‘fight’ by cannibalizing conspecific eggs or neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation